1971
DOI: 10.1136/oem.28.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the aetiology of byssinosis

Abstract: (1971). Brit. J. industr. Med., 28,[143][144][145][146][147][148][149][150][151]. Studies on the aetiology of byssinosis. A condensed polyphenol based on leucocyanidin has been extracted from the cotton plant. The reaction between this material and human serum has been demonstrated using both a precipitin and a passive agglutination technique. Sera from 196 cardroom workers not suffering from byssinosis, 177 byssinotic cardroom workers, and 203 controls were tested for reactivity with the condensed polyphenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…After PVP treatment, all three extracts produced minimal pneumocyte injury, suggesting that tannins may be Edwards has shown that THF is capable of producing lung inflammation (8). Further evidence suggesting a role for THF is presented by Taylor and co-workers (35) who showed, in a double-blind trial, that inhalation of THF at a concentration of 0.5 mg/ml for 15 min produced symptoms of byssinosis in five of six byssinotic patients, but produced no symptoms in nine cotton workers without byssinosis or eleven unexposed controls. In our studies, the injury produced by THF was predominantly THF inhaled in the workplace (37).…”
Section: Discussionmentioning
confidence: 81%
“…After PVP treatment, all three extracts produced minimal pneumocyte injury, suggesting that tannins may be Edwards has shown that THF is capable of producing lung inflammation (8). Further evidence suggesting a role for THF is presented by Taylor and co-workers (35) who showed, in a double-blind trial, that inhalation of THF at a concentration of 0.5 mg/ml for 15 min produced symptoms of byssinosis in five of six byssinotic patients, but produced no symptoms in nine cotton workers without byssinosis or eleven unexposed controls. In our studies, the injury produced by THF was predominantly THF inhaled in the workplace (37).…”
Section: Discussionmentioning
confidence: 81%
“…The reactive constituent was identified as a condensed polyphenol, leucocyanidin (133), and, although the substance has since been shown to precipitate immunoglobulins nonspecifically (40), hence not a true antigen, double-blind inhalation studies indicated that byssinotic symptoms were produced only in byssinotic subjects (133). Whether true circulating antibodies to cotton antigens exist in addition to this phenomenon has not been established.…”
Section: Miscellaneous Hypersensitivity Pneumonitis In-mentioning
confidence: 96%
“…Previous immunologic studies were hampered by inability to demonstrate dust-specific precipitating antibodies in the serum of exposed individuals [9,11,15], and by lack of response in laboratory animals in jected with cotton dust extracts [6,9], In this study we report a specific antibody response in rabbits to aque ous cotton dust extracts (ACDE), and partial charac terization of antigenic and allergenic components in these extracts by crossed immunoelectrophoretic and crossed radioimmunoelectrophoretic techniques.…”
Section: Introductionmentioning
confidence: 99%